Żwirownia obok Theatergebäude jako miejsce zbrodni w KL Auschwitz - Cyra, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
During the 1940–1941 period the executions in KL Auschwitz were also conducted in gravel pits situated behind the camp’s fence. The largest of those, consisting of two pits, was located close to the so-called theatre building „Theatergebäude”. In one of those pits prisoners were executed in 1941. The victims were Polish. Two of those executions were conclusively established but the possibility that there had been more cannot be excluded. Prisoners of the penal company Strafkompanie and education company Erziehungskompanie also worked in this gravel pit. Oftentimes they were cruelly murdered. For instance, on the 27th of June four Polish Catholic priests were killed during laboring in the penal company. On the 1st of September 1941 one of the prisoners escaped from the gravel pit area. This event had particularly disastrous consequences, the victims of which were the inhabitants of Oswiecim County who were attempting to help the fugitive.
Keywords: Auschwitz; ludobójstwo; egzekucje